Achievement of low infrared emissivity photonic crystal design on [CdSe/SiO2]N periodic films. (December 2022) - Tong, Hanxiang; Li, Hongsheng; Huang, Hao; Wu, Aimin; Cao, Tun; Guo, Dongming
Graphical abstract: Highlights: The reflectance from the single-layer interface to the multi-layer films is analyzed. Transfer matrix method is used to calculate the reflectivity of photonic crystals. The effects of structure and material factors on the emissivity are calculated. Abstract: By revealing the transmission matrix of multi-layer thin films system, practical route is provided for preparing the photonic crystals in materials selection and structure optimization on the low infrared emissivity requirements of the specific bands. High infrared reflectivity states are derived based on the conventional materials of CdSe (high refractivity) and SiO2 (low refractivity) through constructing periodic multi-layer film structure [CdSe/SiO2 ]N . Various photonic crystals are designed via changing the central wavelength. The factors of incident angle, period, film thickness, and refractive index on the forbidden band of infrared are calculated to discover the complex influence of the refractive index for low infrared emissivity of the thin films under full operating conditions.